Quality of Clean Water Source of Borehole Wells in Batu Merah Village, Sirimau Subdistrict, Ambon City - Bulan Sari Hamid Tuga; Ferdinand Salomo Leuwol; Edward Gland Tetelepta (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
The water quality in Batu Merah, Sirimau District, Ambon City, which is dominated by hilly and mountainous topography, remains a significant concern. The local community largely relies on borewell water to meet their clean water needs, but their understanding of the water quality is still limited. This descriptive qualitative study involved collecting water samples from the field, which were then analyzed in a laboratory to evaluate physical, chemical, and biological parameters. The results showed that the borewell water quality does not fully meet the required standards. In borewell sample 1, the manganese levels exceeded the permitted maximum, while borewell sample 2 revealed a total coliform count of 1600, and sample 3 recorded a total coliform count of 70, both exceeding the allowable limit of 50 per 100 ml. Therefore, the borewell water in this area has not yet fully met the clean water quality standards as outlined in the Ministry of Health Regulation No. 20 of 2023 and Ministry of Health Regulation No. 416/Menkes/Per/IX/199, particularly regarding chemical and biological parameters.